Analysis of Temporal and Spatial Characteristics of Precipitation Series in Weihe River Basin Based on Sample Entropy - MU Jiaxin; SUN Dongyong; RU Ya'nan; WANG Miaomiao; LI Xianwei; LI Ya'nan (Renmin Zhujiang)
In a changing environment,the temporal and spatial complexity of precipitation in the Weihe River Basin changes.In this paper,the measured daily precipitation data of 21 meteorological stations in the Weihe River Basin in 59 years from 1960 to 2018 are selected.The static and dynamic evolution characteristics of the complexity of precipitation series in the Weihe River Basin are studied by the moving sample entropy (M-SampEn).The mutation test is carried out by the combination of the moving cut sample entropy (MC-SampEn) and Bayesian analysis.The results show that the complexity of precipitation series in the Weihe River Basin has spatial differences,and the precipitation complexity and intergenerational variation trend in each sub-region are relatively consistent.The precipitation of the upper and middle reaches of Weihe River and Jinghe River Basin mutated in 1995,and that of the lower reaches of Weihe River mutated in 1991 while that of the Beiluo River Basin mutated in 1970 and 2000.